Impact of NaCl, KCl, MgCl2, MgSO4 and CaCl2 on the leaf anatomy of cucumber (Cucumis Sativus Cv. Mti2) - Mohammed, Samar Jasim; Nulit, Rosimah (Dr. R.S. Yadab, 2020)
This study was conducted to compare the effects of NaCl, KCl, MgCl2, MgSO4 and CaCl2 on the anatomical of cotyledon leaves. Five types of salts (NaCl, KCl, MgCl2, MgSO4 and CaCl2) at different concentrations (50, 100, 150 and 200 mM) and deionized water as control are used. A 10 sterilized seeds were placed in Petri dishes containing 5 ml of deionized water or each salinity solution and kept in the growth chamber at 25 ± 1°C. On day 8th, coteyledon leaves were fixed for anatomical study. Results show the response of MTi2 on five different salts is significantly different. The degree histological changes of MTi2 cotyledon leaves increased as the concentration of salts increased. Salts significantly change the structure and arrangement of the upper epidermis cells, mesophyll tissue and lower epidermis cells, also reduce of intracellular space among the mesophyll cells. Results found that no anatomical changes of MTi2 cotyledon leave in any concentration of KCl.